2019
DOI: 10.3390/v11070636
|View full text |Cite
|
Sign up to set email alerts
|

Measles Vaccine Virus RNA in Children More Than 100 Days after Vaccination

Abstract: Measles vaccines have been in use since the 1960s with excellent safety and effectiveness profiles. Limited data are available on detection of measles vaccine virus (MeVV) RNA in human subjects following vaccination. Available evidence suggests MeVV RNA can be identified up to 14 days after vaccination, with detection beyond this rare. In routine diagnostic testing, we used two real-time reverse transcription-polymerase chain reaction (RT-rPCR) assays targeting M and F genes to identify measles virus (MeV) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…These measles virus detections by syndromic PCR panels were attributed to previous MMR vaccination because nearly all occurred in persons without risk factors for measles and shortly after receipt of MMR vaccine. Detection of the strain of measles virus used in MMR vaccine typically occurs within 21 days of vaccination, but detection >100 days later has been reported ( 7 ), a period that aligns with findings described here. Children frequently experience symptoms of rash and fever from many causes, including other viral illnesses and typical vaccine side effects.…”
Section: Discussionsupporting
confidence: 87%
“…These measles virus detections by syndromic PCR panels were attributed to previous MMR vaccination because nearly all occurred in persons without risk factors for measles and shortly after receipt of MMR vaccine. Detection of the strain of measles virus used in MMR vaccine typically occurs within 21 days of vaccination, but detection >100 days later has been reported ( 7 ), a period that aligns with findings described here. Children frequently experience symptoms of rash and fever from many causes, including other viral illnesses and typical vaccine side effects.…”
Section: Discussionsupporting
confidence: 87%
“…One study by Murti et al reported that the measles vaccine virus was detected in the nasopharynx five weeks post-vaccination [4] . McMahon et al reported that the measles vaccine virus was detected in children vaccinated with measles up to 548 days after the first MMR vaccination and up to 471 days after the second dose of MMR [5] , and the majority of individuals detected with MeVV were children between the ages 1–4 years [6] . The long-period detection of MeVV may be due to the improved sensitivity of the PCR test.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the measles virus, not just measles-specific antibodies, can be detected in the nasopharyngeal swab specimen for a period after vaccination. However, information on how long the measles vaccine virus (MeVV) in human nasopharyngeal samples will be detected after the vaccination is limited [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Measles can be detected using rRT-PCR during and after wild-type measles infection, as well as through the detection of vaccine-strain measles virus after vaccination with any live attenuated measles-containing vaccine (including MR and MMR). The duration of vaccine-strain detection is unclear; prolonged detection of measles vaccine strain (>100 days after vaccination) has been reported, although such prolonged detection appears to be rare [ 30 ]. The differentiation of vaccine strain from wild-type measles is critical when a person has both recent vaccination (i.e., within 21 days of onset of fever and rash) and an epidemiologic risk for measles, as in this case.…”
Section: Diagnostic Scenarios and Discussion Of Managementmentioning
confidence: 99%